MCDM Bunkering Optimisation in a Hub and Spoke System: The Case of the North Adriatic Ports - Tuljak-Suban, Danijela (Promet - Traffic&Transportation, 2019)
Choosing an optimal bunkering port that minimises the increase in the operating costs in a hub and spoke system is a multi-criteria decision-making (MCDM) problem. Furthermore, the criteria are related to the port particularities, the environment, fuel price, and some criteria are quantitative while others are qualitative. It is therefore necessary to create a model that takes such features into consideration. Firstly, in this paper a set of the most used criteria will be defined. Then, a method to choose suitable criteria for a hub and spoke system will be proposed. Secondly, using a Fuzzy AHP, weights will be defined and used in a multi-criteria goal function. The outcome is a bunkering policy MCDM model based on the aggregation of fuel consumption and price to criteria related to port characteristics, local aspects and service particularities. All these factors must be considered by a chief engineer (superintendent) in the process of defining a sustainable bunker policy. A case study based on the North Adriatic port system demonstrates the applicability of the proposed model. In addition, the case study highlights that in hub and spoke systems with short loops, feeder ships can regulate cargo capacity and stay at a port with bunkering policy planning.